Do Atta sexdens rubropilosa workers prepare leaves and bait pellets in similar ways to their symbiotic fungus? - Silva, L. C. [UNESP]; Camargo, R. S. [UNESP]; Forti, L. C. [UNESP]; Matos, C. A. O. [UNESP]; Travaglini, R. V. [UNESP] (Univ Estadual Feira Santana, 2015)
Leaf-cutting ants rely on the obligate symbiosis with a fungus, Leucoagaricus gongylophorus, on which they feed. This fungus garden is maintained preferentially with green leaves in combination with other tissues of plant origin. The nutritional composition of this symbiotic relationship is extremely beneficial for the colony, representing the main food source for larvae and an important food component of adult workers. The objective of this study was to observe the behavioral repertoire of Atta sexdens rubropilosa during the preparation and incorporation of two different substrates, leaves and bait pellets, as well as the participation of each caste in these processes this process. The first substrate offered to the colonies were Citrus sp. leaves cut into disks and the second were pellets of citrus pulp bait formulated without the active ingredient. The observations were made under a stereomicroscope and were started when the first portion of the substrate offered was carried to the fungus garden. The behaviors executed during preparation and incorporation of the leaf disks, and subsequently of the bait pellets, were recorded using three colonies, with six repetitions of 5 and 7 hours per colony, respectively. Eight behavioral acts were recorded for the three castes found, irrespective of the substrate processed by the workers. Licking was the most frequently executed behavioral act, which occurred throughout the observation period, regardless of the substrate offered. Gardeners and generalists were the castes most engaged in the execution of this behavior. Considering the large number of individuals involved in the execution of this task, it can be concluded that this behavior is important for dispersion of the active ingredient and contamination of workers inside the colony.
Keywords: Social insects; worker contamination; bait processing; leaf-cutting ants; Atta